M. tuberculosis Infection in Patients with HIV Infection and Incidence of Tuberculosis: 8-year Follow-up - E. M. Bogorodskaya; E. M. Belilovskiy; L. B. Ayusheeva; E. N. Posadskaya (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. Patients with HIV infection is of the leading risk groups for tuberculosis. According to WHO, the presence of HIV infection increases the likelihood of developing tuberculosis by 26 times and is the second factor in the world after malnutrition that affects the number of cases of tuberculosis. Aims. Study of primary infection with M. tuberculosis, spread of latent infection and incidence of tuberculosis in HIV-infected patients during 8 years of observation. Materials & Methods. An analysis of the data from the register of requests to the Cabinet was carried out. We studied a cohort of persons living with HIV who first visited the TB office in 2016. We studied information about screening for latent and active tuberculosis infection. We studied information about the course of HIV infection: the date of registration at the AIDS Center, the date of receiving a positive immunoblot result, the level of CD4+ lymphocytes, the stage of HIV infection, information about taking antiretroviral therapy. Results and discussion. The study was conducted on a large array of data obtained in a cohort of patients with HIV infection who first applied in 2016 to the office for the prevention and early detection of tuberculosis of the Moscow Research and Clinical Center for Tuberculosis Control of the Moscow Government Department of Health and was observed for 8 years until 2023. For evaluation of the spread of tuberculosis infection among persons living with HIV, a subgroup of 5754 people was identified for whom the test results with recombinant tuberculosis allergen -ATR, were known in 2016, which amounted to 80.8%. A total of 6,733 ATR were administered, with 15.0% of patients not presenting for evaluation, 1.0% refusing the test, and 3.2% having a medical exemption from the skin test. In this group, over 8 years (2016-2023), 38 (13.1%) people out of 291 patients with ATR(+) and 55 (1.0%) people out of 5503 people with ATR(-) fell ill. During the first 4 years of observation in 2017-2020, 91.7% of all tuberculosis cases were registered for persons living with HIV with LTBI in 2017-2023. Conclusion. The presence of LTBI in patients with HIV infection increases the likelihood of developing tuberculosis by more than 10 times, while the chance of developing tuberculosis is more than five times lower in people with LTBI who have received a full course of preventive treatment for tuberculosis. The lack of preventive therapy for tuberculosis accelerates and increases the likelihood of persons living with HIV contracting tuberculosis: during the first year of observation, 70% of all cases become ill.